1982
DOI: 10.1126/science.7063865
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opiates and Energy Balance

Abstract: Increasing the palatability of food has two opposite effects: it promotes overeating and provokes caloric output (energy expenditure). The increase in energy expenditure is too small to compensate for overeating and, as a result, obesity occurs. Repeated administration of zinc tannate of naloxone, a long-lasting opiate antagonist, completely abolishes this diet-induced obesity in rats. The drug accomplishes this not only by reducing overeating but also by increasing energy expenditure. This suggests that endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 14 publications
2
35
1
Order By: Relevance
“…These alterations were revealed only by an adipogenic dietary challenge because deletion of the MOR had no effect on body weight, fat mass, or glucose metabolism in adult mice fed a low-fat diet. These results agree with the modest effects of long-acting opioid receptor antagonists on the body weight of rats fed a regular diet and the ability of these agents to prevent weight gain in rats fed an adipogenic diet (6,24). However, in contrast to the findings observed with pharmacological agents, the decreased vulnerability to diet-induced obesity observed in mice selectively deficient for the MOR is attributable to changes in energy metabolism and not in caloric intake.…”
Section: Discussioncontrasting
confidence: 35%
See 3 more Smart Citations
“…These alterations were revealed only by an adipogenic dietary challenge because deletion of the MOR had no effect on body weight, fat mass, or glucose metabolism in adult mice fed a low-fat diet. These results agree with the modest effects of long-acting opioid receptor antagonists on the body weight of rats fed a regular diet and the ability of these agents to prevent weight gain in rats fed an adipogenic diet (6,24). However, in contrast to the findings observed with pharmacological agents, the decreased vulnerability to diet-induced obesity observed in mice selectively deficient for the MOR is attributable to changes in energy metabolism and not in caloric intake.…”
Section: Discussioncontrasting
confidence: 35%
“…It has been suggested that opioids favor the conservation of energy because the weight reduction induced by opioid antagonists in rats fed an adipogenic diet exceeded the degree to which caloric intake was reduced (6,24). However, controversial results on energy expenditure have been obtained with pharmacological tools (6,7). Two studies have reported that nonselective opioid antagonists induce a decrease in RQ, thereby indicating an opioid modulation of lipid oxidation, in rats fed regular and high-fat diets (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How ingestion of palatable food is regulated is of great interest to those studying ingestive behavior as well as those studying basic mechanisms of motivation and reward. One of the first neurochemical systems implicated in the hedonics of feeding and obesity was the endogenous opioid system (Belluzzi and Stein, 1977;Mandenoff, et al, 1982;Margules, et al, 1978). In general, opioid antagonists are anorexigenic while opioid agonists are orexigenic [reviewed in (Bodnar, 2004;Glass, et al, 1999)].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%